Successful Transcatheter Handmade-Valved Graft Stent for Branch Pulmonary Regurgitation: Novel Approach in a Special Event - Lin, Ming-Tai; Wang, Jou-Kou; Wu, Pei-Yuan; Lu, Chun-Wei; Chang, Te-I; Chen, Yih-Sharng (The Annals of thoracic surgery, 2016)
Right heart failure is not uncommon in the patients with repaired tetralogy of Fallot (rTOF). Although commercialized transcatheter stent-mounted pulmonary valves are effective treatment options for improving functional class and for normalizing right ventricular volumes in such patients, they are not available in Taiwan. To provide a handmade alternative, we report our successful transcatheter attempt of a handmade assembled left pulmonary artery valved stent graft implantation in a 61-year-old man who had a history of rTOF and severe branch pulmonary regurgitation.